Information Technology Application Audit for Employees Using IT Baseline Protection - Ridwan Satrio, Muhammad; Laksa Wibawa, I Made Bagus Wiradivka; Oka Saputra, Komang (International Journal of Engineering and Emerging Technology, 2019)
In the current era of information technology, data or information is a very valuable asset and must be protected. The IT Baseline Protection Manual provides an effective way of analyzing threats and ways to secure data through a Maturity Level measurement process. This method is applied by the German government to regulate information technology audit standards. In this method there is an audit module in the employee area to analyze how well the application of information technology by employees in an agency. An information technology audit at the Badung Regency Communication and Information Department aims to measure the maturity level of employees in applying information technology using the domains available in the IT Baseline Protection Manual. The audit phase starts from the case study survey, the IT Baseline Manual Protection domain selection and gets the results of the questionnaire which is a measure of maturity level by evaluating using Maturity Level. The Maturity Level figures obtained from the audit of the application of information technology to employees using the IT Baseline Protection Manual domain which is equal to 3.43. The results show that the maturity level of the process of applying information technology to employees at the Communication and Information Department of Badung Regency is at Level 3 (Defined), namely there are already good IT process standards in the entire scope of the organization but could be increased to the maximum.